Innovative Extraction Techniques and Hyphenated Instrument Configuration for Complex Matrices Analysis - Locatelli, Marcello; Carradori, Simone; Mocan, Andrei (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The present Special Issue, (3z(BInnovative Extraction Techniques and Hyphenated Instrument Configuration for Complex Matrices Analysis(3y(B, aims to collect and to disseminate some of the most significant and recent contributions in the interdisciplinary area of innovative extraction procedures from complex matrices followed by validated analytical methods using hyphenated instrument configurations to support the optimization of the whole process and the scale-up possibilitys
English
Keywords: alginate; n/a; heavy metals; high-speed counter-current chromatography (HSCCC); microwave processing; phytochemicals; microNIR; antioxidant activity; in-line monitoring; Wuyi Rock tea; metabolomics; seawater; optimization; walnut septum; color analysis; metabolite profiling; rosuvastatin; dispersive liquid-liquid microextraction; antioxidant; mouse melanoma B16 cells; nails; extraction; sample preparation; quality; MAE; Panax notoginseng; physicochemical properties; flow injection; ionic liquids; branched-chain keto acids; Semen Cuscutae; near-infrared spectroscopy; volatile organic compounds; odor; SFE; single-drop microextraction; experimental design; cluster analysis; therapeutic drug monitoring; Thymus algeriensis; metformin; tyrosinase; gas chromatography-olfactometry; Ajuga genevensis; phytosterols; serum; diabetes; GHB; polyphenols; ultrasound assisted extraction; microextraction; oolong tea; alkaloid; minor ginsenosides; inductively coupled plasma-mass spectrometry; wood; stir bar sorptive extraction; HPLC-Q-TOF/MS; GHB glucuronide; Hericium erinaceuns mycelium